2019
DOI: 10.1101/573360
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selection and co-selection of antibiotic resistances amongEscherichia coliby antibiotic use in primary care: an ecological analysis

Abstract: The majority of studies that link antibiotic usage and resistance focus on simple associations between the resistance against a specific antibiotic and the use of that specific antibiotic. However, the relationship between antibiotic use and resistance is more complex. Here we evaluate which antibiotics, including those mainly prescribed for respiratory tract infections, are associated with increased resistance among Escherichia coli isolated from urinary samples.Monthly primary care prescribing data were obta… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 36 publications
(45 reference statements)
0
7
0
1
Order By: Relevance
“… 36 One study by Pouwels and colleagues noted that the use of specific antibiotics, such as levofloxacin, for E coli urinary tract infections is associated with resistance to other antibiotics used for other indications, such as ciprofloxacin, leading to co-selection of antibiotic resistance E coli isolates. 40 One of the most likely reasons for the unhindered resistance despite decreases in antibiotic prescribing is the accumulation of mutations conferring resistance to antibiotics and acquired antibiotic resistance genes within the bacterial populations. 41 Collignon and colleagues suggested that transmission of antibiotic-resistant genes was likely to be the most dominant contributor to antibiotic resistance, implying that resistance might continue despite a restriction of prescribing.…”
Section: Discussionmentioning
confidence: 99%
“… 36 One study by Pouwels and colleagues noted that the use of specific antibiotics, such as levofloxacin, for E coli urinary tract infections is associated with resistance to other antibiotics used for other indications, such as ciprofloxacin, leading to co-selection of antibiotic resistance E coli isolates. 40 One of the most likely reasons for the unhindered resistance despite decreases in antibiotic prescribing is the accumulation of mutations conferring resistance to antibiotics and acquired antibiotic resistance genes within the bacterial populations. 41 Collignon and colleagues suggested that transmission of antibiotic-resistant genes was likely to be the most dominant contributor to antibiotic resistance, implying that resistance might continue despite a restriction of prescribing.…”
Section: Discussionmentioning
confidence: 99%
“…Cefalexina y cefradina para el manejo de infecciones del tracto respiratorio superior y de vías urinarias no complicadas presentaron una menor proporción de uso, probablemente por ser un manejo alternativo en estas indicaciones 14,18 . El uso de antimicrobianos que son útiles en varias indicaciones podría incrementar el riesgo de www.revinf.cl Antimicrobianos aparición de cepas resistentes, como se ha mostrado para amoxicilina o cotrimoxazol 32 . Dado que las cefalosporinas se pueden emplear en múltiples patologías, se debería limitar su uso en indicaciones en las cuales no sean tratamiento de primera línea, con el fin de protegerlas como recurso, evitando el desarrollo de resistencia bacteriana y desenlaces adversos.…”
Section: Discussionunclassified
“…While, for example, lower levels of amoxicillin prescribing in primary care are associated with lower levels of resistance against amoxicillin and trimethoprim among urinary specimens, 5 this does not necessarily result in a reduction in resistance against antibiotics that are almost exclusively used in the hospital setting 3 . Moreover, within England, the reported number of macrolide‐resistant BSI for Gram‐positive bacteria increased between 2014 and 2018, even though prescribing for macrolides decreased in both hospitals and primary care 3 .…”
mentioning
confidence: 99%